Penerapan Aplikasi Google Classroom Pada Materi Larutan Elektrolit Dan Non Elektrolit Berbasis Problem Based Learning (Pbl) Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA Negeri 1 Lawa - Waode Kiki Tamsar; Rustam Musta; Maysara (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
Research on the Application of Google Classroom media based on Problem Based Learning on the subject of Electrolyte and Non-Electrolyte Solutions, aims: to find out descriptions of student learning achievement, increase in student learning achievement, significant differences in the use of google classroom and print modules. Type of research: quasi experiment with Pretest-Posttest Control Group Design. Research instruments: test questions and response questionnaires. The research sample was students in class X MIPA 1 and X MIPA 3. The results of this study showed that: The learning achievement of students using the problem-based learning-based google classroom increased from an average pretest of 29.32 to 81.68 in the posttest. The conclusion of the study: The implementation of the Google Classroom application on problem-based learning-based electrolyte and non-electrolyte solution material has an effect on increasing student outcomes